Challenges of Pancasila in the Field of Government: Corruption, Collusion and Nepotism in Government - Farid Sri Wardana (Aimmah: Social Sciences Journal, 2026)
As the basic ideology of the Indonesian state, Pancasila serves as a philosophical and moral guideline for running a just, civilized, and honest government. However, due to the prevalence of corruption, collusion, and nepotism (KKN) in the Indonesian government system, the values ​​of Pancasila are often neglected. Challenges posed by the KKN phenomenon include reducing bureaucratic integrity, disrupting the rule of law, and reducing public trust in government institutions. The purpose of this paper is to examine the relationship between KKN practices and the crisis in the implementation of Pancasila values ​​in the Indonesian government from 2020 to 2025. To investigate the root causes, empirical evidence, and efforts to revitalize Pancasila values ​​​​in realizing clean and accountable governance, this article uses a qualitative descriptive approach based on a literature review. The research shows that public officials have not truly adopted the moral principles of Pancasila, despite various efforts to reduce corruption, such as increasing the power of the Corruption Eradication Commission (KPK) and implementing a digital government system. To build an ethical and just government, the values ​​of Pancasila must be incorporated into the education system, bureaucracy, and law enforcement.